Studies toward the First Stereoselective Total Synthesis of (±)-Quinolizidine 195C and Other Transformations - Shang-Shing P. Chou; Jhih-Liang Huang (Molecules, 2013)
Starting from a thio-substituted 4-quinolizidinone, a series of C-6 alkylated derivatives with a trans C-6, C-9a relationship was synthesized. Further transformations led to the first stereoselective total synthesis of the structure proposed for (±)-quinolizidine 195C, the major alkaloid isolated from the skin extracts of the Madagascan frog Mantella betsileo. Since the spectral data of the synthetic and natural products differed significantly, the true structure of (±)-quinolizidine 195C remains uncertain.